1989
DOI: 10.1002/1097-0142(19890801)64:3<765::aid-cncr2820640333>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal cortical carcinoma

Abstract: The records of 110 patients (58 females and 52 males) with histologically proven adrenal cortical carcinoma were studied. Fifty-six of 110 (50.9%) patients had abdominal symptoms and 33 (30.0%) had a palpable abdominal mass. Surgery for localized and regional disease was associated with a disease-free survival time of at least 2 years in 28 of the 50 (56%) patients. Abdominal radiotherapy, systemic chemotherapy, and 1,1 dichloro-2 (O-chlorophenyl)-2 (P-chlorophenyl) ethane (OPDDD) were effective in three of 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
91
1
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(107 citation statements)
references
References 12 publications
11
91
1
4
Order By: Relevance
“…Other authors have previously suggested a similar favourable effect (Hutter & Kayhoe, 1966b;Lubitz et al, 1973;Venkatesh et al, 1989), but to our knowledge this has never been well documented. Moreover, in a large retrospective study Luton et al (1990) could not find an independent beneficial effect resulting from mitotane therapy.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Other authors have previously suggested a similar favourable effect (Hutter & Kayhoe, 1966b;Lubitz et al, 1973;Venkatesh et al, 1989), but to our knowledge this has never been well documented. Moreover, in a large retrospective study Luton et al (1990) could not find an independent beneficial effect resulting from mitotane therapy.…”
Section: Discussionsupporting
confidence: 58%
“…Adjuvant mitotane therapy has been advocated after complete tumour resection (Venkatesh et al, 1989;Luton et al, 1990). In our study, patients who were treated adjuvantly with mitotane did not do better than those who did not receive it.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations